Divergências inconciliáveis e pactuações convenientes: elaboração e implementação da política de educação do campo em municípios baianos - Cristo, Claudiano da Hora de (2015)
This research problematized the cycle of social policies of Rural Education in the sense of understand the contribution of social agents of the State and civil society in the formulation process and problematization of its effectuation. It has as study objective the performance of Collective of the Project get to know, Analyze and Transform the reality of the field (CAT Project) in the mobilization of the social policy agenda of Rural Education in Bahia municipalities. This research had as guiding question: what is the contribution of the Collective Project "CAT" to the formulation and questioning of effectuation of social policies in the Field Education for a compound set of 26 municipalities in the state of Bahia, in the period of 2003 - 2010. Faced with this question was formulated the following overall goal: to analyze the actions and propositions of the CAT Collective Project in the formulation and problematization process of the implementation of social policies of Rural Education in the basic system of elementary school. The epistemological approach that directs this research is the critical-dialectic whose matrix is the historical-dialetic materialism. This survey was operationalized through data analysis technique, whose main source were the Annual Reports of the CAT Project, the year 2003 to 2010, which record the activities developed by the Collective of this Project. As analysis categories stand out: social policies and popular education. Conducted by theoretical - Methodological references we can analyze the social policies of Rural Education in Brazil and its particular expression, the Project CAT and we found that the CAT Collective Project, despite some contradiction, put on the agenda the Rural Education policy. However, in relation of a local situation, national and international hegemony of neoliberal policy, which resulted in a loss of radical social movements, building consensus among antagonistic social classes and focused on public policies, geared to alleviate poverty and, Therefore, social conflicts, the actions of CAT Collective Project did not succeed.